Strategi Word of Mouth dan Digital Marketing terhadap Kinerja Penjualan Layanan Internet: Studi Manajemen pada PT Telkomsel Cabang Demak - Muhammad Khanif Ismail; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the influence of Word of Mouth and digital marketing on the sales performance of internet services at PT Telkomsel Demak Branch, as well as to examine the integration of both strategies from the perspective of integrated marketing communication. This study is grounded in service marketing theory, consumer behaviour, and integrated marketing communication, with a focus on the role of interpersonal communication and digital media in shaping consumer purchasing decisions at the local branch level. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 active customers selected using a purposive sampling technique. The research instrument was tested for validity and reliability and was deemed appropriate for use. Data analysis was conducted using multiple linear regression to examine both partial and simultaneous effects among variables. The results show that Word of Mouth and digital marketing simultaneously have a significant effect on the sales performance of internet services. Partially, Word of Mouth has a more dominant influence compared to digital marketing, indicating that customer experience and recommendations remain the primary factors in shaping purchasing decisions within the local market context. These findings emphasise that marketing effectiveness is not only determined by the intensity of digital promotion but also by the quality of customer experience that drives word-of-mouth communication. The theoretical contribution of this study lies in strengthening an integrative model of Word of Mouth and digital marketing in explaining sales performance in the telecommunications industry at the branch level, particularly in local market contexts with strong social characteristics. Thus, this study provides empirical novelty that the synergy of both strategies is more effective than their separate implementation in improving internet service sales performance.